Teachers’ self‐reported L1 and L2 use and self‐assessed L2 proficiency in primary EFL education - Wilden, Eva; Porsch, Raphaela (Studies in Second Language Learning and Teaching, 2020)
This study investigates teachers’ first language (L1, German) and second language (L2, English) use in the primary English as a foreign language (EFL) classroom in two federal German states. It particularly focuses on the question of whether a more frequent, (self-reported) use of the L2 is positively correlated to teachers’ professional qualification as well as (self-assessed) L2 proficiency. To this end, data was collected in 2017 through an online survey among German primary teachers teaching EFL in year 4 (N = 844). L2 use was assessed through a 4-point Likert scale comprising 16 items on various classroom situations. L1 use was surveyed with an open question on situations of L1 use in the L2 classroom. Moreover, teachers self-assessed their L2 proficiency with a 4-point Likert scale and adapted CEFR descriptors for speaking. Findings indicate that teachers claim to use the L2 more in L2-related situations and the L1 more in classroom management situations. The study shows that teachers with a higher formal qualification tend to assess their L2 proficiency higher and claim to use the L2 more often in the primary EFL classroom. In contrast, teachers with a lower formal qualification tend to assess their L2 proficiency lower and claim to use the L1 more frequently in the L2 classroom.